5-week suspension training program increase physical performance of youth judokas: a pilot study (Un programa de entrenamiento de suspensión de 5 semanas incrementa el rendimiento físico en jóvenes judocas: un estudio piloto) - Norambuena, Yessenia; Winkler, Lorena; Guevara, Rocío; Lavados, Pamela; Monrroy, Manuel; Ramírez-Campillo, Rodrigo; Herrera-Valenzuela, Tomás; Gajardo-Burgos, Rubén (Retos, 2021)
5-week suspension training program increase physical performance of youth judokas: a pilot studyUn programa de entrenamiento de suspensión de 5 semanas incrementa el rendimiento físico en jóvenes judocas: un estudio piloto*Yessenia Norambuena, *Lorena Winkler, *Rocío Guevara, *Pamela Llavados, *Manuel Monrroy, **Rodrigo Ramírez-Campillo, ***Tomás Herrera-Valenzuela, *Rubén Gajardo-Burgos*Universidad Austral de Chile (Chile), **Universidad de Los Lagos (Chile), ***Universidad Santo Tomás (Chile)Abstract. Introduction: Judo is a high-intensity sport, characterized by a series of acyclic movements that require high technical mastery during combat. It was previously shown that growth of components of physical function is related with an increased probability successful competitive performance. Suspension training is effective at improving components of physical function. Objective: Therefore, the aim of this study was to determine the changes in physical performance traits of youth judokas after a 5-week suspension-training programme. Methods: Ten judokas (age, 15.4 ± 2.8 y) completed a 5-week suspension training routine into their normal training schedule. The difficulty and intensity of the exercises were increased each week. Before and after the intervention athletes were assessed in the single-leg horizontal jumping, Sorensen test, sit-and-reach, Y balance, prone instability and handgrip strength tests. Results: Significant improvements (p